Crisis and mutation of the public health service in Spain - Cantero Martínez, Josefa (2016)
The aim of this paper is to analyze the effects that recent health reforms adopted in Spain because of the economic crisis have had on the National Health System. It is not only a matter of mere budgetary cuts or measures of saving in the public expense. Reforms are looking for the efficiency and financial sustainability of health care services. However, a «mutation» in the public service has taken place. Reforms have affected the basic principles of the public system: the insurance model, its universality, the financing of the system and the principles of equity and cohesion of the public service.